The Extent to which Dimensions of Strategic Recovery of Service have been achieved in some Departments of the Presidency of University of Baghdad - KADHEM, HAIDER FADHEL; HAFEDH, ABDULNASER ALAG (The journal of contemporary issues in business and government, 2021)
The research aims to explicit the role of Strategic Recovery of Service (SRS). It relies on how organizations response to the failure of provided services and seeks to reduce the level of failure in order to gain the beneficiaries’ confidence, satisfaction and loyalty. The research problem is not paying enough attention to (SRS) dimensions, compensation- distributive justice, speed of recovery- procedural justice, and apology- initiation - interactional justice, through dealing with some issues regarding to employees’ stratification, productivity, and quality of outputs. The importance of research stems from highlighting the weaknesses and implications of not take into consideration (SRS) dimensions in an administrative workplace. The (Checklist) was employed to check the extent of application of (SRS) dimensions at some departments within the Presidency of the University of Baghdad. The current layout of the researched organization does not achieve the required convergence among departments to complete their assigned tasks in time and reduce overall efforts and costs.